Oxytocin accelerates tight junction formation and impairs cellular migration in 3D spheroids: evidence from Gapmer-induced exon skipping - Jurek, Benjamin; Denk, Lucia; Schäfer, Nicole; Salehi, Mohammad Saied; Pandamooz, Sareh; Haerteis, Silke (Frontiers in Cellular Neuroscience, 2022)
Oxytocin (OXT) is a neuropeptide that has been associated with neurological diseases like autism, a strong regulating activity on anxiety and stress-related behavior, physiological effects during pregnancy and parenting, and various cellular effects in neoplastic tissue. In this study, we aimed to unravel the underlying mechanism that OXT employs to regulate cell-cell contacts, spheroid formation and cellular migration in a 3D culture model of human MLS-402 cells. We have generated a labeled OXT receptor (OXTR) overexpressing cell line cultivated in spheroids that were treated with the OXTR agonists OXT, Atosiban, and Thr4-Gly7-oxytocin (TGOT); with or without a pre-treatment of antisense oligos (Gapmers) that induce exon skipping in the human OXTR gene. This exon skipping leads to the exclusion of exon 4 and therefore a receptor that lost its intracellular G-protein-binding domain. Sensitive digital PCR (dPCR) provided us with the means to differentiate between wild type and truncated OXTR in our cellular model. OXTR truncation differentially activated intracellular signaling cascades related to cell-cell attachment and proliferation like Akt, ERK1/2-RSK1/2, HSP27, STAT1/5, and CREB, as assessed by a Kinase Profiler Assay. Digital and transmission electron microscopy revealed increased tight junction formation and well-organized cellular protrusions into an enlarged extracellular space after OXT-treatment, resulting in increased cellular survival. In summary, OXT decreases cellular migration but increases cell-cell contacts and therefore improves nutrient supply. These data reveal a novel cellular effect of OXT that might have implications for degenerating CNS diseases and tumor formation in various tissues.